Protein expression profiles in methicillin-resistant Staphylococcus aureus (MRSA) under effects of subminimal inhibitory concentrations of imipenem. Issue 15 (16th September 2019) - Wang, Jichun; Wang, Junrui; Wang, Yanyan; Sun, Peng; Zou, Xiaohui; Ren, Luo; Zhang, Chunxia; Liu, Enmei
ABSTRACT: Imipenem is a beta-lactam antibiotic mainly active against gram-negative bacterial pathogens and also could cause cell wall impairment in methicillin-resistant Staphylococcus aureus (MRSA). However, related antibacterial mechanisms of imipenem on MRSA and mixed infections of MRSA and gram-negative bacteria are relatively poorly revealed. This study was to identify proteins in the MRSA response to subminimal inhibitory concentrations (sub-MICs) of imipenem treatment. Our results showed that 240 and 58 different expression proteins (DEPs) in sub-MICs imipenem-treated S3 (a standard MRSA strain) and S23 (a clinical MRSA strain) strains were identified through the isobaric tag for relative and absolute quantitation method when compared with untreated S3 and S23 strains, respectively, which was further confirmed by multiple reactions monitoring. Our result also demonstrated that expressions of multiple DEPs involved in cellular proliferation, metabolism and virulence were significantly changed in S3 and S23 strains, which was proved by gene ontology annotations and qPCR analysis. Further, transmission electron microscopy and scanning electron microscopy analysis showed cell wall deficiency, cell lysis and abnormal nuclear mitosis on S23 strain. Our study provides important information for understanding the antibacterial mechanisms of imipenem on MRSA and for better usage of imipenem on patients co-infected with MRSA and other multidrug-resistant gram-negative bacteria. Abstract : The differentially expressed proteins induced by imipenem in methicillin-resistant S. aureus were associated with formation of ribosomal, pigment, biofilms and cell wall, and autolytic activity.